Modelling and Analysis of Hysteresis in Piezoelectric Actuator - Singh, A.K.; Apte, Deepak (Defence Science Journal, 2006)
Piezoelectric actuators are the potential actuators having a wide range of applications in smart structures and systems. However, the presence of hysteresis nonlinearity leads to degradation in their performance. This paper discusses a mathematical model for hysteresis in piezoelectric actuators based on domain wall bending and translation1. The validity of the model has been illustrated through comparison with the experimental observations of piezoelectric stack actuator developed using PZT5H material.